LexO: an open-source system for managing OntoLex-Lemon resources. - Bellandi, Andrea (Language Resources & Evaluation, 2021)
The adoption of Semantic Web technologies and the Linked Data paradigm has been driven by the need to ensure the construction of resources that are at the same time interoperable, shareable and reusable by the scientific community. OntoLex-Lemon, which exploits the expressive power of ontologies, has come to be the de facto standard model for the representation of lexica and terminologies. The number of users potentially interested in editing or consuming OntoLex-Lemon data is thus very large. Unfortunately, the use of ontology editors for constructing such language resources can be very tedious due to the complexity and verbosity of the model, which heavily relies on specific modeling technicalities. This underlines the importance of developing tools and services that facilitate the creation and editing of resources and bring lexicography and terminology closer to the Semantic Web. In this paper we present LexO, a collaborative web editor for easily building and managing lexical and terminological resources in the context of the Semantic Web, based on the OntoLex-Lemon model. It makes the model accessible to users who do not possess the needed technical skills, thus allowing for wider adoption of new technological advances in the Semantic Web.